Accountability of Indemnity Implementation Toward Land Liberation Dam Development of Pammukkulu, Takalar District - Erwing Yanto; Mohamad Thahir Haning; Muhammad Yunus (Enrichment : Journal of Management, 2021)
The construction of the dam in the village of Kale Ko'mara has reached the first stage, the construction has resulted in 30 residential settlements being freed and about 30 hectares of agricultural land and rice fields have been freed, but the acknowledgment of the affected residents there is still some land that has not been from the community. has been in development in this first stage, The purpose of this paper is to analyze to compensate for the land for the construction of the Pammukkulu dam in Takalar Regency. The research method used in this paper is a qualitative method. The results of this study indicate that the accountability of the implementation of compensation for dam construction is reviewed from the perspective of the community. In the framework of paying compensation for land required for the development and implementation of an appropriate, clear, measurable and legal accountability system so that governance and development can take place in an efficient, effective, clean and responsible manner. Before land acquisition is carried out, it is necessary to hold a public debate to convey perceptions so that all developments can run effectively and efficiently, and carry out good socialization and interaction. In order for the implementation of compensation to run well, the relevant government needs to coordinate with all agencies and communities so that the working apparatus remains well controlled, and the community can support land acquisition.